КОМУНІКАТИВНИЙ ПОТЕНЦІАЛ МИСТЕЦТВА В РЕАЛІЯХ ІНФОРМАЦІЙНОГО СУСПІЛЬСТВА - Mokliak, L. (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Introduction. The first quarter of the 21st century has witnessed profound civilizational shifts driven by technological advancement, global crises, and growing existential tension. In times of war, migration, and destructive transformation, an individual’s spiritual self-grounding and ability to preserve identity through engagement with culture have become especially vital. Art, as a form of active communication, offers a path toward deeper dialogue, empathy, and the preservation of a sense of human being. The aim and tasks. This article aims to explore the communicative potential of art, its essence, and its specific characteristics within the cultural context of the information society. It also seeks to reveal the role of art in the current system of cultural communication. Research methods. The main method employed is the dialectical approach, applied at all levels of analysis to uncover the features of art as a communicative system. In addition, sociocultural and interdisciplinary methodologies are used to examine the issue through socio-philosophical, aesthetic, cultural, and psychological perspectives. Research results. The specificity of artistic communication is distinguished by its ability to transform communication to its highest level that is interaction. Interaction is characterized by subject–subject engagement, dialogical openness, reciprocity, and empathy. Art, as a form of spiritual culture and a specific sphere of creative activity, also serves as a distinct and powerful form of social communication. It is a living, direct, spiritual-emotional process of interaction between the creator and the recipient (viewer, listener, reader), mediated through the artwork itself. Discussion. Art, as a unique form of aesthetic communication, enables a profound dialogical encounter between creator and recipient, fostering understanding beyond language or culture. Through such interaction, it reveals universal human values and becomes a powerful medium for spiritual connection and emotional transformation. Conclusions. In today’s information society, communicative technologies often contribute not to inner harmony, but to the erosion of spiritual and value-based orientations. Art, by contrast, preserves the capacity to attune the "spiritual tuning fork of humanity," evoking empathy, hope, and faith in human dignity. To protect and nurture this potential, it must be supported both by educational and cultural policy and by individual moral responsibility.